Comparison of UV‐Cl and UV‐H2O2 advanced oxidation processes in the degradation of contaminants from water and wastewater: A review - Farzanehsa, Mahshid; Vaughan, Liam C.; Zamyadi, Arash; Khan, Stuart J. (Water and environment journal : WEJ, 2023)
Applications of advanced oxidation processes (AOPs) in water and wastewater treatment have been the subject of growing interest throughout the last decade. Although UV/hydrogen peroxide (UV‐H2O2) is the most established technology among the UV‐AOPs, UV‐chlorine (UV‐Cl) is emerging as a reliable and potentially more cost‐effective alternative. Recent studies have indicated that UV‐Cl processes may be more efficient and economically favourable for the degradation of some chemicals of emerging concern from contaminated water. Moreover, in terms of the formation of disinfection by‐products (DBPs), UV‐H2O2 seems to have no superiority over UV‐Cl. This said, more investigation in the assessment of genotoxicity and cytotoxicity of DBPs is required. Additionally, more pilot‐scale and full‐scale studies are required to establish UV‐Cl as a reliable alternative to UV‐ H2O2. This paper compares UV‐Cl and UV‐H2O2 AOPs for the degradation of intractable chemicals from water and wastewater based on the practical considerations of efficiency, cost, DBP formation, kinetics and sensitivity to water matrix variability. Finally, various modelling approaches to UV‐Cl have been reviewed. This review showed that UV‐Cl is superior to UV‐H2O2 in terms of degradation efficiency and cost effectiveness and can be a robust alternative in many UV‐AOPs applications.